THE POTENTIAL OF RETICULOCYTE HAEMOGLOBIN EQUIVALENT (RET-HE) IN IRON DEFICIENCY ANAEMIA SCREENING AT BETHESDA HOSPITAL, YOGYAKARTA - fenty fenty fenty (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
Background: Traditionally, iron deficiency anaemia (IDA) is diagnosed with iron and ferritin status. Ret-He measurement is a promising parameter to detect iron depletion in earlier stages. Previous studies recommended Ret-He examination as IDA screening. Objective: Compare the Ret-He level and iron status of patients with and without IDA at Bethesda Hospital, Yogyakarta. Method: This is a cross-sectional study using laboratory record of haematological examination at Bethesda Hospital from march to August 2019. Erythrocyte indices, iron status and Ret-He measurement was further examined between IDA and non-IDA group by ANOVA, t-test or non-parametric tests. Results: There were 105 samples, where 22 (20.95%) had complete result of Ret-He and iron status, and 10 (45.45%) diagnosed with IDA. The Ret-He level in IDA group is significantly lower than non-IDA group (17.53 ± 2.43 vs 31.50 ± 4.03, p < 0.001). Conclusion: Ret-He level is lower in IDA group, consistent with other biochemical parameters (Serum iron, Serum ferritin, TIBC, and TSAT). This finding might lead to future research on the potential of Ret-He for early detection of IDA in high-risk populations.